Testing second language speaking - Fulcher, Glenn (Applied linguistics and language study., 2014)
The testing and assessment of second language learners is an essential part of the language learning process. Glenn Fulcher''s Testing Second Language Speaking is a state-of-the-art volume that considers the assessment of speaking from historical, theoretical and practical perspectives. The book offers the first systematic, comprehensive and up-to-date treatment of the testing of second language speaking. Written in a clear and accessible manner, it covers:Explanations of the process of test design Costing test design projects How to put the test into practice Evaluation of speaking tests Task.